Design and Implementation of an automation trainining panel with PLC and HMI applied to a filling system using servomotors for the power electronics laboratory. - YUMBLA AREVALO, FRANCISCO XAVIER (2016)
EL PAPER SOLO SE ENCUENTRA EN INGLES